2022
DOI: 10.1111/jgh.15837
|View full text |Cite
|
Sign up to set email alerts
|

Vonoprazan non‐inferior to lansoprazole in treating duodenal ulcer and eradicating Helicobacter pylori in Asian patients

Abstract: Background and Aim Duodenal ulcers, especially caused by increasingly drug‐resistant Helicobacter pylori, are a concern in Asia. We compared oral vonoprazan versus lansoprazole for efficacy (healing duodenal ulcers) and safety in non‐Japanese Asian patients. Methods In this phase 3, randomized (1:1), double‐blind, double‐dummy, parallel‐group, non‐inferiority study (April 5, 2017, to July 19, 2019), patients with ≥ 1 endoscopically confirmed duodenal ulcer, at 52 hospitals (China, South Korea, and Taiwan), rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 39 publications
1
37
1
Order By: Relevance
“…Vonoprazan was similar to PPIs (7-VAC and 14-OAC groups: 96.7% and 88.5%, p=0.083, respectively) in the analysis with the intention-to-treat and 98.3% and 93.1%, p=0.159, respectively, in the per protocol). Hou et al 36 Furthermore, the results of the per-protocol analysis were comparable to those of the intention-to-treat analysis (89.3% vs. 90.1%, P=0.06).…”
Section: Primary-line Treatmentmentioning
confidence: 72%
“…Vonoprazan was similar to PPIs (7-VAC and 14-OAC groups: 96.7% and 88.5%, p=0.083, respectively) in the analysis with the intention-to-treat and 98.3% and 93.1%, p=0.159, respectively, in the per protocol). Hou et al 36 Furthermore, the results of the per-protocol analysis were comparable to those of the intention-to-treat analysis (89.3% vs. 90.1%, P=0.06).…”
Section: Primary-line Treatmentmentioning
confidence: 72%
“…1 ). Of the gastric acid‐related diseases, six were erosive esophagitis, 18 , 19 , 20 , 21 , 22 , 23 two were symptomatic GERD, 24 , 25 nine were H. pylori infection, 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 three were gastric ulcers, 34 , 35 , 36 and the remaining two were duodenal ulcers 33 , 35 (Table 1 ). All studies were peer‐reviewed published clinical trials except for two unpublished clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…In trials conducted by X. Hou et al [42] and H. Miwa et al [43] found vonoprazan 20 mg to be no inferior to lansoprazole 30 mg in the treatment of DU, with similar side effects. They also observed that gastrin levels were higher in patients treated with vonoprazan.…”
Section: Vonoprazan and Duodenal Ulcers (Du)mentioning
confidence: 96%